The Small IRAIT telescope. Photometric time-series during the polar night - R. Briguglio; K. G. Strassmeier; H. Bruntt; R. Nesci; L. Sabbatini; TOSTI, Gino (2009)
The Small IRAIT is a 25 cm telescope which was deployed and installed at Dome C, on the high antarctic plateau, in 2007. During the polar night an intensive photometric program was carried out: despite the harshness of the polar winter, the telescope worked in a semi-robotic way giving us a large amount of photometric data and precious informations about technology and procedures for polar missions.